EDGEWORTH BINOMIAL MODEL FOR PRICING OPTIONS - LESSY (NIM : 20110004), DJAFFAR
In this thesis, will be discussed pricing options with Edgeworth binomial model. The model is constructed using the Edgeworth expansion that uses the first four moments which the specifications are skewness and kurtosis. The options that the price is specified are European option and barrier option. European option pricing is divided into two models, namely the first Edgeworth binomial model that uses Edgeworth binomial approach and the second Edgeworth binomial model that uses Edgeworth binomial tree construction. In the simulation of pricing European option dan barrier option, for different time of maturity are used different skewness and kurtosis that determined using historical price data.